Research progress of Mo−Re alloy structural materials usedfor nuclear reactors - ZENG Yi; SUN Yuanjun; AN Geng; DING Xiangdong; QIU Xi; WANG Na; SUN Jun (Fenmo yejin jishu)
Molybdenum (Mo) as the refractory metals shows the series of advantageous properties, such as high melting point, excellent high temperature mechanical properties, and good thermal conductivity. In addition, the good antiradiation swelling ability and high compatibility with liquid metals make Mo as the important candidate materials for the advanced nuclear reactors to endure the high temperature, strong corrosion, and high-dose irradiation, such as the fourth generation high-temperature nuclear fission reactor and the fusion reactor. Nevertheless, the application of Mo is limited by the brittle nature at low temperature, the difficult machining, and the poor welding performance. Adding rhenium (Re) into molybdenum to form "rhenium effect" can not only significantly improve the room temperature plasticity and the processability of molybdenum and reduce the plastic brittle transition temperature, but also improve the welding performance and creep resistance. Therefore, it has become a research hotspot of structural materials for the advanced nuclear reactors. The research progress of molybdenum−rhenium alloys (Mo−Re) was summarized in this paper from four aspects as composition design, material preparation, welding performance, and nuclear environmental application assessment, and the problems of Mo−Re alloys used for the advanced reactor engineering were analyzed to provide the reference for the development of high-performance molybdenum−rhenium alloy structural materials.